Development and Comprehensive Evaluation of Ecological Agriculture Industry Chain System Based on Genetic Algorithm. (10th September 2022) - Jia, Peiyao; Chu, Jiankun; Niu, Wenjia; Jia, Puyao; Zhang, Ling
Abstract : Due to the constraints of traditional agricultural development factors, the existing agricultural industrial chain structure was unreasonable, which can not only promote the development of related industries but also affect the sustainable development of the whole agriculture. Therefore, it was of great significance to build a scientific and orderly ecological agriculture industry chain system and optimize it on the existing basis for improving the industrial benefits of modern agriculture and enhancing the vitality of agricultural development. From the perspective of the construction of an ecological agriculture industry chain system, this study put forward the development and evaluation system of the agricultural industry chain system based on genetic algorithm, in order to provide support for better promoting the development of modern agriculture. First, based on summarizing the related concepts of ecological agriculture and industrial structure, the definition and organization of agricultural industrial chain were given. Second, it expounded the basic theory of genetic algorithm and its application in the optimization of agricultural industrial structure, and put forward the optimization model of ecological agricultural industrial structure combined with the objectives of agricultural industry development. Finally, by constructing the evaluation index system of ecological agriculture industry chain system, a comprehensive evaluation model of ecological agriculture industry chain system based on genetic algorithm was designed. Through the case verification and comparative analysis, the results showed that the ecological agriculture industry chain system evaluation system and evaluation model based on genetic algorithm proposed in this study had certain feasibility and effectiveness, and can better evaluate the changing trend of various industries in the process of agricultural industry development.